(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2020)
The digital turn in anthropology and ethnography is not a sudden rupture to the field’s epistemological quest. In recent years, after the visual turn and the evolution of Digital Humanities, there have been notable efforts to address the digital aspect of social reality by several anthropologists worldwide. However, the focus has been predominantly on the observation of internet cultures and communities, mainly tackling phenomena that ‘take place’ in the digital realm, and on the techniques and issues that arise from conducting online research with limited contributions to the theoretical ramifications of recent advancements on the technological front. We argue that the methodological repercussions of the discussion around digital ethnographic writing modalities has not yet been adequately addressed, which reflects a wider tendency of the anthropological lens to remain on the “observant” side of things and not partake in the active discussion and practices regarding knowledge production and representation. Drawing on the research project “Ethnography and/as hypertext fiction: representing surrogate motherhood” (HYFRESMO), currently implemented at the Anthropology Department of Panteion University and funded by the Hellenic Foundation for Research and Innovation & the General Secretariat for Research and Technology, the paper seeks to provide an example of the creative accommodation of digital media in the field of anthropology. In order to do so, it focuses on the intersections between the object of study (new reproductive technologies) and the writing tropes made available by new digital technologies. After conducting ‘traditional’ physical fieldwork on surrogate motherhood, and combining offline and online observation and communication with research interlocutors, our methodological proposition does not aspire to radicalize the work already implemented by fellow anthropologists in the direction of data gathering or performing participant observation in the digital/cyber-sphere; rather, in our endeavor to create a transmedia, non-text-oriented, fictional ethnographic account (during but mainly after) the fieldwork experience, we propose that digital ethnographic representation becomes a very privileged under-researched terrain upon which to experiment on the transformative potential of the digital turn in the humanities and creatively tie together the research topics and their representational potentials.